Magnetohydrodynamic Three Dimensional Flow and Heat Transfer Past a Vertical Porous Plate Through a Porous Medium with Periodic Suction - Das, SS; Mitra, M; Mishra, PK (Bangladesh Journal of Scientific and Industrial Research, 2012)
This paper analyzes the effect of magnetic field and the permeability of the medium on the three dimensional flow of a viscous incompressible electrically conducting fluid through a porous medium bounded by an infinite vertical porous plate in presence of periodic suction and a transverse magnetic field. The governing equations for the velocity and temperature of the flow field are solved employing perturbation technique and the effects of the pertinent parameters such as magnetic parameter (M), suction parameter (α), permeability parameter (Kp), Reynolds number (Re) and Prandtl number (Pr) on the velocity field, temperature field, skin friction and the rate of heat transfer are discussed with the help of figures and tables. It is observed that both magnetic parameter and the permeability parameter have accelerating effect on the velocity of the flow field. The effect of growing Prandtl number/suction parameter/ Reynolds number is to enhance the temperature of the flow field at all points while a growing magnetic parameter has retarding effect on the temperature field. The magnetic parameter increases the x-component of skin friction and reduces the magnitude of z-component of skin friction at the wall while the permeability parameter shows the reverse effect on both the components of skin friction. The rate of heat transfer at the wall grows as we increase the magnetic parameter or suction parameter or Prandtl number in the flow field and the effect reverses with the increase of the permeability parameter. Key words: MHD; Three dimensional flow; Heat transfer; Vertical plate; Porous medium; Periodic suction DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9593 BJSIR 2011; 46(4): 465-474